Chiral background for the two-pion exchange nuclear potential: A parametrized version - Da Rocha, C. A. [UNESP]; Robilotta, M. R. (American Physical Society (APS), 1995)
We argue that the minimal chiral background for the two-pion exchange nucleon-nucleon interaction has nowadays a rather firm conceptual basis, which entitles it to become a standard ingredient of any modern potential. In order to facilitate applications, we present a parametrized version of a configuration space potential derived previously. We then use it to assess the phenomenological contents of some existing NN potentials. © 1995 The American Physical Society.